Implementasi Kegiatan Ekstrakurikuler Al-Banjari dalam Meningkatkan Karakter Religius Peserta Didik di MA Ma’arif 7 Sunan Drajat Paciran Lamongan - Ahmad Fairuz Prahasana; Muhammad Najib; Nur Fatih Ahmad (Jurnal Studi Multidisiplin Qomaruna, 2026)
Religious character formation is an essential part of Islamic education to develop individuals with moral integrity. This study examines the implementation of Al-Banjari extracurricular activities as a means of fostering students' religious character at MA Ma’arif 7 Sunan Drajat Paciran Lamongan. Using a qualitative approach and case study method, data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model: data reduction, display, and conclusion drawing. The results show that Al-Banjari activities have been structured since 2009 with clear task division, guided training, and strong school support. These activities not only enhance Islamic musical talent but also build discipline, responsibility, and teamwork. Students’ religious character is evident in their understanding of religious values (moral knowing), emotional involvement in religious practices (moral feeling), and consistent worship and behavior (moral action). The study concludes that Al-Banjari contributes significantly to strengthening religious character through practical, contextual Islamic cultural experiences. It recommends further development of Islamic arts-based extracurricular programs as a strategy for character building in education.